Simultaneous external and internal marking of Triatoma sordida nymphs: trace element efficacy and microgeographic dispersal in a peridomestic Brazilian Cerrado rural household - Edson Santos Dantas; Rodrigo Gurgel-Gonçalves; Rafael Maciel-de-Freitas; Fernando Araújo Monteiro (Parasites & Vectors, 2022)
Abstract Background Chagas disease (American trypanosomiasis) is an important neglected tropical illness, which has the flagellate protozoan Trypanosoma cruzi as etiological agent and blood-feeding insects of the Triatominae subfamily as vectors. Despite its importance for disease epidemiology, field studies targeting microgeographic dispersal of triatomines in endemic areas are rare. The ability wingless nymphs have to move (crawl) within peridomestic settings is a key component regarding the design and development of rational control strategies. Methods We double-marked Triatoma sordida fourth-instar nymphs (N4) with a reliable fluorescent dye and a trace element. This new methodology allowed us to simultaneously evaluate (i) nymph dispersal and (ii) the effectiveness of copper (Cu), chromium (Cr), and cadmium (Cd) trace elements as potential new markers. In the mark-release-recapture (MRR) experiment, 390 T. sordida N4 were released in the peridomicile of a single rural household, 130 individuals at each of three release points, at distances of 2, 5, and 10 m from the chicken coop (CC) and 27, 32, and 35 m away from the horse corral (HC). All specimens were double marked (Cu/blue, Cr/orange, Cd/green). Recaptures occurred in two intervals: 1–3 days and 15–17 days after release. Results Specimens were successfully recaptured at all distances up to 10 m. A total of 19, 23, and 10 specimens were able to disperse 2, 5, and 10 m, respectively, to reach the CC. No insects were recaptured at the HC. Of the three analyte/paint combinations tested, Cr/orange gave the most promising results; Cu/blue marker and Cd/green marker performed very poorly with only 4/19 and 0/10 analyte/paint ratios, respectively. Conclusions Triatoma sordida N4 could cover a distance of 10 m in 17 days. This indicates that nymphs seem to have a reduced dispersal capability compared to adults. Ninety-one percent of the 22 recaptured orange-marked nymphs were still Cr positive after the 17-day period evaluated. This makes this analyte a good candidate for future investigations that will apply this marking method in MRR studies. Graphical Abstract